Spin dynamics of triaxial nuclei with a quasiparticle alignment - Budaca Radu; Budaca Andreea-Ioana (EPJ Web of Conferences)
The dynamics of nuclei with a triaxial core and a non-axial rigid quasiparticle alignment is described with a Schrödinger equation constructed from a semiclassical formalism. The use of the total angular momentum projection as a continuous variable and the separation of the potential energy allows the interpretation of the spectra in terms of anharmonic wobbling oscillations and tilted axis rotations. The experimental realization of the model is presented for the h11/2 quasiparticle bands of the 133La nucleus, which is found to exhibit a novel tilted-axis wobbling mode of excitation.